Paradoks Empati: Tinjauan Sistematis Komunikasi Antarpribadi Manusia dalam Pelayan Pelanggan Berbasis Kecerdasan Buatan Hibrida - Elza Evelina Amanta Simanjuntak; Naztia Maulida Putri; Fera Widianata; Santa Clara Sitanggang; Iza Alfira; Wilda Sarwangi; Aulia Risky (Indo Publishing, 2026)
The development of digital technology, particularly Artificial Intelligence (AI), has brought about significant changes in the way companies communicate with customers. The use of AI in customer service, such as chatbots and virtual assistants, provides convenience through faster, more efficient, and more accessible services. However, these developments also pose challenges in interpersonal communication, particularly regarding AI's ability to convey empathy, which is typically found in human interactions. This study aims to analyze how the use of Artificial Intelligence affects interpersonal communication in a Hybrid AI-Driven Customer Services system and to identify the role of empathy in building a better customer experience. This study used the Systematic Literature Review (SLR) method by analyzing various scientific articles related to Artificial Intelligence, interpersonal communication, empathy, Computer-Mediated Communication (CMC), and customer satisfaction. The results show that AI makes a positive contribution to improving service effectiveness through automation, response speed, and ease of access to information. However, AI still has limitations in deeply understanding customer emotions because it lacks the emotional experience of humans. Therefore, implementing a Hybrid AI-Driven Customer Services system provides a solution by combining the capabilities of AI technology with the role of humans. While AI can help address simple customer needs, humans are still needed to provide empathy and resolve more complex issues. This research demonstrates that the development of AI in customer service should not only focus on technological efficiency but also consider interpersonal communication aspects to create a more personalized and meaningful customer experience.